Methodical instructions for individual work on topic "Design and development of applications to work with relational databases using PHP, Java and Python" - Kopp, Andrii Mykhailovych; Orlovskyi, Dmytro Leonidovych; Ved, Olena Valeriivna; Vasylenko, Artem Viktorovych (Національний технічний університет "Харківський політехнічний інститут", 2025)
As part of the individual task, students acquire theoretical knowledge and practical skills necessary for work in the field ofinformation technology: — definition and formulation of functional and non-functional requirements for a software product; — design and development of software components to create an application that works with a database; — use of development tools and software interfaces of client-server database management systems (DBMS) using MySQL as an example. Students are not limited in their choice of architecture, software development platform, and development tools. In this work, it is necessary to create a complete web-oriented, desktop or mobile software solution that will work with a designed and developed database according to functional and non-functional requirements. The purpose of the work is to provide students with practical skills necessary for designing and developing databases, as well as formulating requirements, designing, developing, and testing software.
Keywords: methodical instructions; independent work; application design; application development; relational databases; PHP, Java and Python